2012
DOI: 10.3846/13923730.2012.719835
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modeling Integrated With Electronic Commerce Material Procurement and Supplier Performance Management System

Abstract: Traditional construction material procurement is being replaced by electronic commerce construction material procurement now. Building Information Modeling (BIM) has shown benefit and practical value in construction material quantity takeoff and cost estimate. However, very few efforts have been directed to the application and integration of BIM in e-commerce material procurement.The author compares the present commercial BIM and non-BIM based quantity takeoff and cost estimate software, presents one solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 31 publications
(55 reference statements)
0
25
0
1
Order By: Relevance
“…Developments in this particular field are fast-changing and recently a number of authors either proposed (Ren et al, 2012) or reported on the development of the work that is underway to initiate e-trading activities directly through the Cloud-based BIM models (Grilo and Jardim-Goncalves, 2011;Costa and Grilo, 2015). However, as also acknowledged by these authors, lack of standardization of procurement processes and problems with interoperability of product data presents a complex challenge for collaborative and transactional processes across BIM models and e-Marketplace systems.…”
Section: Electronic Trading Technologies In the Aec Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Developments in this particular field are fast-changing and recently a number of authors either proposed (Ren et al, 2012) or reported on the development of the work that is underway to initiate e-trading activities directly through the Cloud-based BIM models (Grilo and Jardim-Goncalves, 2011;Costa and Grilo, 2015). However, as also acknowledged by these authors, lack of standardization of procurement processes and problems with interoperability of product data presents a complex challenge for collaborative and transactional processes across BIM models and e-Marketplace systems.…”
Section: Electronic Trading Technologies In the Aec Industrymentioning
confidence: 99%
“…In addition to the XML-based messages, the Industry Foundation Classes (IFC) and STEP file formats (which are primarily used in design and construction stages of a project) allow embedding of the building specification data within its content (Shen et al 2010). Ren et al (2012) explain that the information stored in these files maybe part of the 3D model file which contain additional intelligent data about the 3D building objects and elements, or separate from the model file itself. However, since their application aimed primarily for the design, construction and expost processes in a project's life cycle, the use of the IFC and STEP file types for the transactional exchange is currently limited to cost information sharing: for example, data from an IFC can be exported into CIS/ 2 exchange standard for cost analysis of structural steel (BuildingSmart, 2015).…”
Section: Implementation Of Commercial Information Exchange By Aec Firmsmentioning
confidence: 99%
“…Redmond et al (2012) used cloud computing as integration platform to enhance the BIM usability experience for various disciplines in making key design decisions at the early design stage. Ren et al (2012) presented a proposed solution to link BIM-derived data with RS Means unit price cost data to generate accurate cost estimating reports. Mill et al (2013) provided a critical appraisal of the process of both collecting accurate survey data using a terrestrial laser scanner and creating a BIM model as the basis of a digital management model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many benefits of BIM cited in the previous work in supporting decisions and improving processes throughout the lifecycle of a project (Eastman et al 2008;Shen, Issa 2010;Manning, Messner 2008;Succar 2009;Becerik-Gerber, Rice 2010). Related to the design phase of a project, these benefits include parametric modeling, identification of design conflicts and analysis, green design, design simulation, cost estimation, and accurate geometric representation of all facilities Li et al 2006;Eastman et al 2008;Shen, Issa 2010;Staub-French, Khanzode 2007: Manning, Messner 2008Fox, Hietanen 2007;Shen et al 2012;Lee et al 2012a, b, c;Ren et al 2012). During the construction phase, these benefits include less rework, reduction in requests for information and change orders, customer satisfaction through visualization, improved productivity in phasing and scheduling, faster and more effective construction management with easier information exchange, accurate cost estimation, and visualizing safety analysis (Eastman et al 2008;Hardin 2009;Matta, Kam 2010;Azhar 2011;Zhou et al 2012;Hartmann et al 2012).…”
Section: Introductionmentioning
confidence: 99%